Proximate, mineral and melissopalynological analyses of honeys produced by Apis mellifera adansonii maintained at the University of Lagos Apiary (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
This study focused on the management of established Apis mellifera adansonii colonies, and evaluation of the proximate, mineral, and pollen contents of honeys produced by these bees at the University of Lagos apiary. Two newly established bee colonies were managed using modern hive management techniques. Honeys produced by these colonies were subjected to further laboratory analyses. Proximate composition of honey samples was determined based on the official analysis methods from Association of Official Analytical Chemists (AOAC). Mineral composition was determined quantitatively using atomic absorption spectroscopy (AAS). Melissopalynological analysis was conducted to ascertain the amount, type and origin of pollen present in the samples. On the basis of the proximate composition, colony 1 honey had higher carbohydrate (81.29%), crude fibre (1.43%) and ash contents (0.70%) while colony 2 honey recorded higher protein (2.72%), crude fat (0.17%), moisture content (17.32%) and pH (4.6). Result of the mineral analysis showed that potassium was the most abundant element, while manganese was the least present trace element in both honeys. Investigated honey samples contained 8609 pollen and spore types belonging to 27 families and 29 species. Colony 1 honey had the highest pollen diversity, while colony 2 honey recorded the highest abundance. Hippocratea sp. was the predominant pollen type in colony 1 honey sample while Phyllantus sp. was the secondary dominant species in colony 2 honey. Celastraceae and Rubiaceae were the most dominant families recorded in the investigated honey samples. Investigated honey samples were multifloral, rich in minerals, and met the standard requirements of good honey as recommended by International Honey Commission. The study provided the basis for identification of major plants visited by Apis mellifera honeybees within the apiary. There is a need to conserve the existing flora within the study location, especially those found to be rewarding to Apis mellifera adansonii.
Keywords: melissopalynology; mineral analysis; modern hive management; proximate analysis